Tracking antibiotic resistance genes and class 1 integrons in Escherichia coli isolates from wastewater and agricultural fields - Zahra Shamsizadeh (IWA Publishing, 2021)
Considering high concentrations of multidrug-resistant bacteria and antibiotic resistance genes (ARGs) in wastewater, agricultural reuse of treated wastewater may be a public health threat due to ARG dissemination in different environmental compartments, including soil and edible parts of crops. We investigated the presence of antibiotic-resistant Escherichia coli as an indicator bacterium from secondary treated wastewater (STWW), water- or wastewater-irrigated soil and crop samples. ARGs including blaCTX-m-32, blaOXA-23, tet-W, sul1, cml-A, erm-B, along with intI1 gene in E. coli isolates were detected via molecular methods. The most prevalent ARGs in 78 E. coli isolates were sul1 (42%), followed by blaCTX-m-32 (19%), and erm-B (17%). IntI1 as a class 1 integrons gene was detected in 46% of the isolates. Cml-A was detected in STWW isolates but no E. coli isolate from wastewater-irrigated soil and crop samples contained this gene. The results also showed no detection of E. coli in water-irrigated soil and crop samples. Statistical analysis showed a correlation between sul1 and cml-A with intI1. The results suggest that agricultural reuse of wastewater may contribute to the transmission of antibiotic-resistant bacteria to soil and crop. Further research is needed to determine the potential risk of ARB associated with the consumption of wastewater-irrigated crops. HIGHLIGHTS Antibiotic-resistant E. coli presented different abundance in STWW, irrigated soil and crops.; Antibiotic resistance genes were detected in high numbers of E. coli isolates.; sul1 was the most abundant ARG in the E. coli isolates.; Wastewater irrigation could aggravate antibiotic resistance in soil and crops.;